2006
DOI: 10.1002/j.0022-0337.2006.70.5.tb04114.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Implant Dentistry in the Predoctoral Curriculum: A Report from the ADEA Implant Workshop's Survey of Deans

Abstract: In 2004, a survey of the deans of U.S. and Canadian dental schools was conducted to determine the implant dentistry curriculum structure and the extent of incorporating implant dentistry clinical treatment into predoctoral programs. The questionnaire was mailed to the deans of the fifty-six dental schools in advance of the ADEA Implant Workshop conference held in Arizona in November 2004. Out of the fifty-six, thirty-nine responded, yielding a response rate of 70 percent. Thirty-eight schools (97 percent) repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
84
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 6 publications
12
84
1
3
Order By: Relevance
“…A survey by Weintraub et al in 1995 indicated that 86% of dental schools participating in the survey had implemented a predoctoral implant dentistry program 8 and a similar level of interest was noted by Lim et al in 2005 9 . Petropoulos et al, 10 in a survey of deans of US and Canadian dental schools, reported that 97% of dental schools have didactic instruction, and 86% have clinical implant experience at the predoctoral level; however, only 13% of the schools that provide clinical experience have a predoctoral clinical competency requirement in implant prosthodontic procedures 10 …”
mentioning
confidence: 77%
“…A survey by Weintraub et al in 1995 indicated that 86% of dental schools participating in the survey had implemented a predoctoral implant dentistry program 8 and a similar level of interest was noted by Lim et al in 2005 9 . Petropoulos et al, 10 in a survey of deans of US and Canadian dental schools, reported that 97% of dental schools have didactic instruction, and 86% have clinical implant experience at the predoctoral level; however, only 13% of the schools that provide clinical experience have a predoctoral clinical competency requirement in implant prosthodontic procedures 10 …”
mentioning
confidence: 77%
“…While the previous studies of implant education in universities have reported on the involvement of various specialty departments, including specifying the departments teaching implant prosthodontics or surgery, this study presents the involvement of different disciplines in teaching implant maintenance. From this study, implant maintenance teaching in formal university qualifications and university‐based CPD programmes in Australia appears to have very strong involvement of dental specialists and periodontists in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys of implant education, primarily in Europe and North America, have been conducted in the last two decades, including European consensus workshops in 2009 and 2014 . Most of these studies surveyed opinion and/or faculty leaders on the teaching of implant dentistry in undergraduate/predoctoral degree programmes, generally reporting on the topic areas included, expected competencies or clinical requirements, specialty departments/faculty involved and challenges/limitations. A few surveys reported on implant dentistry inclusion in postgraduate specialty programmes and implant‐focused CPD programmes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the improvement of dental implants, the demand for implant treatment has increased exponentially . To accommodate this increasing demand and to prepare future dentists with necessary skills, several dental schools in the United States and abroad incorporated implant training in the curriculum . A strong correlation was found between implant training and use of implant restoration in practice after graduation.…”
mentioning
confidence: 99%